Wealth inequality, uninsurable entrepreneurial risk and firms markup - Samuel Brien (Queen's University, Department of Economics, 2021)
This paper examines the effect of wealth concentration on firms' market power when firm entry is driven by entrepreneurs facing uninsurable idiosyncratic risks. Under greater wealth concentration, households in the lower end of the wealth distribution are more risk averse and less willing (or able) to bear the risk of entrepreneurial activities. This has implications for firm entry, competitiveness, and market power. I calibrate a Schumpeterian model of endogenous growth with heterogeneous risk averse entrepreneurs competing to catch up with firms. This model is unique in that both household wealth distribution and a measure of firm markup are endogenously determined on a balanced growth path. I find that a spread in the wealth distribution decreases entrepreneurial firm creation, resulting in greater aggregate firm market power. This result is supported by time series evidence obtained from the estimation of a structural panel VAR with OECD data from eight countries.
Keywords: E22; E25; L12; O31; O33; O34; 330; Wealth inequality; market power; growth; Schumpeterian; endogenous growth; entrepreneur